Prevalence and factors associated with hyperglycemia among children living with HIV on dolutegravir in Kabale district, southwestern Uganda - Liban Hussein Idow; Timothy Nduhukire; Siyadora Ankunda; Sam Tumwesigire; Filbert Nyeko; James K. Tumwine (PLoS ONE, 2025)
Background Undiagnosed and poorly managed high blood sugar levels can result in short- and long-term complications in children. Following worldwide introduction of dolutegravir based antiretroviral treatment in 2018, several studies in adult people living with HIV have reported high prevalence of hyperglycemia. Little is known about hyperglycemia in children living with HIV on dolutegravir treatment combinations in Uganda. Objectives To determine the prevalence and factors associated with hyperglycemia in children living with HIV on dolutegravir in Kabale district, southwestern Uganda. Methods In a cross-sectional study, 271 HIV infected children on dolutegravir (DTG) were recruited using proportional to size and simple random sampling methods from 18 health facilities that provide Anti-retroviral therapy (ART) services in Kabale district. HIV infected children aged below 18 years were considered eligible to participate in the study. Data was collected using structured questionnaires. Blood samples were taken for random blood sugar and HbA1C. Data was analyzed using STATA 17.0 for both descriptive and inferential statistics. Logistic regression analysis was done, crude and adjusted odds ratios obtained. Results The prevalence of hyperglycemia was 20.3% (95% CI; 15.9–25.5): Of the children with hyperglycemia, 76% (42/55) had prediabetes and 24% (13/55) had diabetes mellitus. Red meat consumption (AOR:3.52; 95% CI: 1.4–9.0, p = 0.009) and being above 13 years of age (AOR:2.61; 95% CI 1.4–4.87, p = 0.003) were independently associated with hyperglycemia. Conclusion One in every five children with HIV on DTG had hyperglycemia. Among those with hyperglycemia, 24% had diabetes mellitus. Hyperglycemia was more likely to be present in adolescents and those who consumed red meat. Regular monitoring of blood sugar in children living with HIV on DTG is recommended.